Impact of Motivation and Discipline on Employee Productivity at Department of Population and Civil Registration of Badung - Indraswari Giri; Putu Yudy Wijaya; Ni Wayan Wina Premayani (Management and Applied Social Studies Review, 2024)
Purpose – To know effect of motivation and discipline on employee productivity in Population and Civil Registration Badung Regency. Methodology – The subjects of research are all employees of the Population and Civil Registration Service Badung Regency, with a total of 47 individuals. The sampling technique used saturated sampling so that 47 respondents were obtained. The research instrument consists of a questionnaire along with several other data collection methods, including observation, interviews, questionnaires and literature studies. The analytical method used is multiple linear regression analysis with SPSS. Findings – The study findings reveal that work motivation and work discipline positively and significantly influences employee productivity at the Population and Civil Registration Service of Badung Regency. Originality – The findings of this research can contribute to the advancement of knowledge in general, particularly in the field of human resource management to work motivation, work discipline and employee productivity and then also serve as a reference if further research is conducted related to this title.